Electrical remodelling and response following cardiac resynchronization therapy: A novel analysis of intracardiac electrogram using a quadripolar lead. Issue 3 (27th April 2018) - Toner, Liam; Flannery, Darragh; Sugumar, Hariharan; Ord, Michelle; Lin, Tina; O'Donnell, David
Abstract: Background: Cardiac resynchronization therapy (CRT) improves morbidity and mortality in patients with heart failure. Although structural remodelling correlates with improved long‐term outcomes, the role of electrical remodelling is poorly understood. This study aimed to evaluate electrical remodelling following CRT using a quadripolar left ventricular (LV) lead and to correlate this with structural remodelling. Methods: Consecutive patients undergoing initial CRT implantation using a quadripolar LV lead were enrolled. Patients were followed up for 12 months. Twelve lead ECG, transthoracic echocardiogram, and evaluation of intracardiac electrograms (EGM) were performed. Measures included right and left ventricular lead intrinsic delay, RV‐pacing to LV‐sensing (RVp‐LVs) delay, and LV‐pacing to RV‐sensing (LVp‐RVs) delay. The electrical changes were then correlated with echocardiographic response to CRT, defined by ≥15% relative reduction in LVESV and ≥ 5% absolute improvement in EF on TTE. Activation sequence was determined using the quadripolar lead. Results: Forty patients were enrolled. Mean intrinsic RV‐LV EGM values decreased from 121.9 ± 14.7 ms to 109.1 ± 15.0 ms ( P < .01), mean RVp‐LVs EGM values from 146.7 ± 16.7 ms to 135.1 ± 13.1 ms, ( P < .01), and mean LVp‐RVs EGM values from 155.7 ± 18.1 ms to 144.2 ± 17.1 ms ( P < .01). The improvement in intrinsic RV‐LV EGM was 14.9 ± 8.5 ms in responders vs 8.9 ± 7.9 ms in nonresponders to CRT ( P < .05). Changes in activation sequence did not correlate with CRT response. Conclusions: This novel study used EGMs from a quadripolar LV lead to demonstrate electrical remodelling occurs following CRT. A nonsignificant trend suggests that electrical remodelling in CRT is greater in responders compared to nonresponders, although further study is needed.